Análisis de vulnerabilidades y amenazas de la red GPON del ISP TEKLINK CIA. LTDA. - Sanmartín Vásquez, Pablo Alexander (2023)
Currently, the global evolution of telecommunications and technology has generated a demand to be at the forefront. Users seek to meet these needs, which is why companies are implementing new technologies to provide improved broadband services. One of these technologies is the GPON (Gigabit-capable Passive Optical Networks) network. This research focuses on the GPON network of the company TEKLINK CIA. LTDA., which was implemented to offer new services to its customers and generate better competition in its environment. It begins with the study of the implemented infrastructure, detailing each of the elements, verifying quality standards, and identifying vulnerabilities of the ODN. It continues with the GPON network tests, which help to determine critical points. These tests are developed from different scenarios, validating the implemented security policies. Finally, this research presents procedures to improve the security of the GPON network of the company TEKLINK CIA. LTDA., which are related to existing ones and will help maintain a more secure network. Keywords: GPON network, vulnerabilities, threats, ISP.